Adjuvant 17-hydroxyprogesterone caproate in women withultrasound-indicated cerclage: a systematic review and meta-analysis. (16th September 2020) - Lichter, Katie E.; Sheffield, Jeanne; Graham, Ernest M.; Eke, Ahizechukwu C.
Abstract: Objective: To assess the additional benefits of 17-hydroxyprogesterone caproate (17-OHPC) therapy in preventing recurrent spontaneous preterm birth in women with an ultrasound-indicated cerclage. Methods: Electronic databases (Medline, Scopus, ClinicalTrials.gov, PROSPERO, Embase, Scielo, and the Cochrane Central Register of Controlled Trials) were searched for studies published before September 2018. Keywords included "preterm birth", "ultrasound-indicated cerclage", "pregnancy" and "17-hydroxyprogesterone caproate". Studies comparing ultrasound-indicated cerclage alone to cerclage plus 17-OHPC were included. The primary outcome measure was preterm birth at <35 weeks of gestation. Secondary outcome measures include preterm birth <24 weeks, <28 weeks, <32 weeks and <37 weeks of gestation, necrotizing enterocolitis (NEC), fetal birth weight, and intraventricular hemorrhage (grades III and IV). Meta-analysis was performed using the random effects model of DerSimonian and Laird. Risk of bias and quality assessment was performed using the risk of bias in nonrandomized studies of interventions (ROBINS-I). Results: Four studies met inclusion criteria and were included in the final analysis. Of the 396 women who received ultrasound-indicated cerclage, 142 (35.9%) received adjuvant 17-OHPC. The primary outcome, preterm birth <35 weeks of gestation, was present in three studies and 332/396 singleton pregnancies. Though there was a trend towards a reduced risk of preterm birth, the summary estimate of effect was not statistically significant when comparing cerclage alone to cerclage plus 17-OHPC at <35 weeks (relative risk (RR) 0.95, 95% CI 0.77–1.17). Similarly, we found no differences in preterm birth at <24 weeks (RR 0.30, 95% CI 0.06–1.60), <28 weeks (RR 0.57, 95% CI 0.13–2.53), and <32 weeks (RR 0.99, 95% CI 0.44–2.27) when comparing cerclage alone to cerclage plus 17-OHPC. There were no differences in fetal birth weight, intraventricular hemorrhage and necrotizing enterocolitis comparing cerclage alone to cerclage plus 17-OHPC. Conclusion: Intramuscular 17-OHPC in combination with ultrasound-indicated cerclage in women with prior preterm birth had no additional effect in reducing spontaneous recurrent preterm birth or improving perinatal outcomes.